Peran Self-Efficacy dan Beban Akademik terhadap Resiliensi Mahasiswa Baru pada Semester Awal - Tarigan, Angeline Hosana Zefany; Appulembang, Yeni Anna; Purnamasari, Ayu (Universitas Muhammadiyah Metro, 2026)
This study examined the roles of self-efficacy and academic load on resilience among first-semester university students. A correlational design was used with purposive sampling of 298 students. Measures included a 25-item self-efficacy scale (α = .911), a 20-item academic load scale (α = .901), and a 24-item resilience scale (α = .934). Descriptive analyses, classical assumption tests, and multiple linear regression (OLS) with Huber-White robust correction were performed. Results indicated that self-efficacy had a positive significant effect on resilience (B = 0.603, p < .001), while academic load had a negative significant effect (B = -0.120, p = .045). The model accounted for 43.7% of variance in resilience (Adjusted R² = .437). Practical implications include focusing on self-efficacy enhancement and academic load management in student support programs.